A Comprehensive Analysis of Covid-19 Research in Turkish Dentistry - Duran, Merve Hacer; Baybars, Sümeyye Coşgun; Gök, Tuba (M. Tayyib KADAK, 2024)
To analyze, classify and summarize current data in Turkish dentistry literature related to COVID-19 in 2-year duration from beginning of the pandemic to the end of 2021. The terms ‘‘COVID-19”, “koronavirüs”, “diş hekimliği”, “pandemic”, “coronavirus”, “dentistry”, “pandemics”, “SARS-Cov-2”’’ were searched separately and in combinations in PubMed and Google Academic databases. Regardless of whether the studies were in Turkish and/or English, it was taken into account that they belong to Turkish dentists, interventional and/or observational, and have been published in the duration starts from the beginning of the pandemic to the end of 2021 and contain information on the COVID-19 pandemic in dentistry. 46 studies in PubMed database and 74 studies in Google Scholar were identified. Studies were classified under 8 main topics (knowledge level and behavioral assessment, psychological effects, research specific to dentistry departments, practices, education, importance of the pandemic, infection control and precautions, social media and social network analysis). Through the findings of the analysis, it will be ensured that dentists and healthcare professionals serving in the field of dentistry will be updated on their knowledge, attitudes and behaviors, be prepared for possible future pandemic situations and shape their perspectives on infectious diseases under the guidance of the literature.

Pandemi başlangıcından 2021 yılı sonuna kadar 2 yıllık süreçte COVID-19 ile ilgili Türk diş hekimliği literatüründeki güncel verileri analiz etmek, sınıflandırmak ve özetlemektir. PubMed ve Google Akademik veri tabanlarında “koronavirüs”, “diş hekimliği”, “pandemic”, “coronavirus”, “dentistry”, “pandemics”, “SARS-Cov-2” terimleri ayrı ayrı ve kombinasyon halinde arandı. Türkçe ve/veya İngilizce olmasına bakılmaksızın Türk diş hekimlerine ait olan, girişimsel ve/veya gözlemsel olan ve pandemi başlangıcından 2021 yılı sonuna kadar yayımlanan ve diş hekimliğinde COVID-19 salgını hakkında bilgi içeren çalışmalar değerlendirildi. PubMed veri tabanında 46, Google Scholar'da 74 çalışma tespit edildi. Çalışmalar 8 ana başlık (bilgi düzeyi ve davranış değerlendirmesi, psikolojik etkiler, diş hekimliği bölümlerine özgü araştırmalar, uygulamalar, eğitim, pandeminin önemi, enfeksiyon kontrolü ve önlemler, sosyal medya ve sosyal ağların analizi) altında sınıflandırıldı. Analiz bulguları ile diş hekimliği alanında hizmet veren diş hekimleri ve sağlık meslek mensuplarının bilgi, tutum ve davranışlarının güncellenmesi, gelecekte yaşanabilecek olası pandemi durumlarına karşı hazırlıklı olmaları ve bulaşıcı hastalıklara bakış açılarını literatürün rehberliğinde şekillendirmeleri sağlanacaktır.
Türk Diş Hekimliğinde Covid-19 Araştırmalarının Kapsamlı Bir Analizi
Keywords: Dentistry; Diş Hekimliği